The role of health literacy as a factor associated with tooth loss - Carla Fabiana Tenani; Manoelito Ferreira Silva Junior; Carolina Matteussi Lino; Maria da Luz Rosário de Sousa; Marília Jesus Batista (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE The objective was to analyze the role of health literacy (HL) as a factor associated with tooth loss among users of the Brazilian Health System with chronic non-communicable diseases. METHODS The cross-sectional analytical study was conducted with adult and elderly users chosen at ten Family Health Clinics in a draw in the town of Piracicaba, São Paulo State, Brazil. A questionnaire was applied with sociodemographic data (sex, age, skin color and education), behavioral data (brushing and flossing), determinants in health (type of dental health services and how often) and clinical data (pain). Mouth conditions were collected by intraoral examination of visible dental biofilm and community Pediodontal Index. The systemic clinical conditions (blood glucose, glycated hemoglobin and blood pressure) were extracted from the medical records. The explanatory variable was HL (low, medium and high), measured with the Health Literacy Scale (HLS-14). RESULTS The outcome was tooth loss measured by the index of decayed, missing and filled teeth. Logistic regression was performed using a conceptual model for HL (p < 0.05). For the 238 subjects, the mean age was 62.7 years (± 10.55). Tooth loss was associated with HL in regression models adjusted by type of dental service, dental frequency, and dental floss. In the final model, the factors associated with tooth loss are older age (OR = 1,12; 95%CI: 1,07-1,17), a lower education (OR = 3,43; 95%CI: 1,17-10,10), irregular use of dental floss (OR = 4,58; 95%CI: 1.75 in-7,31), irregular use of dental services (n = 2,60; 95% 1,32-5,12), periodontal pocket (> 4 mm) (n = 0,31; 95%CI: 0,01-0,08), having visible dental biofilm (OR = 7,23; 95%CI: 3,19-16,41) and a higher level of blood sugar (glucose) (n = 1,98; 95%CI: 1.00-3,92). CONCLUSIONS tooth loss was associated with HL when adjusted by health behaviors; when sociodemographic variables and clinical conditions were included, it was less significant. In the final model, behaviors, determinants in health and clinical conditions were risk indicators of tooth loss, showing the multifactorial nature of this phenomenon.